Effect of Bottom ASH on Shrinkage Reduction of Concrete - Hemavibool, Saranagon (Naresuan University Engineering Journal, 2019)
This research was aimed to study the effect of the nonground bottom ash (BA) obtained from 2 different sources in Thailand, as an internal curing material,on autogenous and total shrinkage behavior of concrete.Three types of bottom ash having different water retainability, i.e. BAH, BAB and BAMM were used in this study andthe percentages of water retainability of these bottom ashes were 18.8, 21.1 and 29.6, respectively.The percentages of replacement of natural fine aggregate with these bottom ashes were 10 and 30% by volume of fine aggregate and the water to cement ratios of concrete mixtures used in this study were 0.35 and 0.55.The results showed that the use of saturated nonground bottom ashes in concrete mixtures as the internal curing material can reduce both autogenous and total shrinkage of concrete. The shrinkage of concrete reduces with the increase of the bottom ash content. The mixtures with higher water retainability bottom ash had lower shrinkage